Euroregionalny program rozwoju zrównoważonego w euroregionie Sprewa-Nysa-Bóbr - Rumianowska, Irena (Euro-Regional Sustainable Development Programme in the Sprewa-Nysa-Bóbr Euroregion, 2007)
The paper describes objectives and conditions of sustainable development principles realization in the Sprewa-Nysa-Bóbr Euroregion. In the Euroregion, there are common elements of environment (catchments, forest areas, hydrological system, natural resources) as well as common problems connected with environment pollution and ecological effects of mining activities. Sufficient problems' solution requires co-operation and co-working of Polish and German partners. Currently, the programme "Sustainable development in Euroregion Sprewa-Nysa-Bóbr" is being led in. The programme includes the following objectives: assuring spatial, economic, social and ecological cohesion of the region, enterprise support, improving the educational level and ecological awareness and the rational use of environment resources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 126-146